Upper limb onset of hereditary transthyretin amyloidosis is common in non‐endemic areas. (11th December 2018) - Théaudin, M.; Lozeron, P.; Algalarrondo, V.; Lacroix, C.; Cauquil, C.; Labeyrie, C.; Slama, M. S.; Adam, C.; Guiochon‐Mantel, A.; Adams, D.; ,
Abstract : Background and purpose: The aim is to describe an uncommon phenotype of hereditary ATTR neuropathy with upper limb onset. Methods: The French TTR Familial Amyloid Polyneuropathy database was used for a retrospective evaluation of 32 consecutive patients with upper limb onset of the neuropathy (study group) and they were compared to 31 Portuguese early‐onset patients and 99 late‐onset patients without upper limb onset. Results: Initial upper limb symptoms were mostly sensory. Lower limb symptoms began 2.3 ± 3 years after upper limb symptoms. Twenty‐four (75%) patients were initially misdiagnosed, with 15 different diagnoses. More patients in the study group had a Neuropathy Impairment Score upper limb/lower limb ratio > 1 compared to the late‐onset patient group. The study group had significantly more pronounced axonal loss in the median and ulnar motor nerves and the ulnar sensory and sural nerves. On radial nerve biopsies ( n = 11), epineurial vessels were abnormal in six cases, including amyloid deposits in vessel walls (3/11), with vessel occlusion in two cases. Conclusion: Upper limb onset of hereditary ATTR neuropathy is not rare in non‐endemic areas. It is important to propose early TTR sequencing of patients with idiopathic upper limb neuropathies, as specific management and treatment are required.